TINJAUAN UNDANG-UNDANG NOMOR 39 TAHUN 2004 TENTANG PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA DI LUAR NEGERI TERHADAP PERLINDUNGAN HAK DAN DARI TINDAK KEKERASAN KEPADA TENAGA KERJA INDONESIA DI KOREA SELATAN - OKVIANA, VIKA (Dinamika Hukum, 2015)
Legal research aims to determine the extent of Law No. 39 of 2004 concerning the Placement and Protection of Indonesian Workers Abroad can provide protection against violence to the rights of Indonesian Workers in South Korea. This research is a juridical sociological law that is descriptive. The location of research in Social Service Manpower and Transmigration (Dinsosnakertrans) Surakarta and Service Agency for Placement and Protection of Indonesian Workers (BP3TKI) Semarang, Institute for Education and Skills (LPK) Kamsahamnida Surakarta, Institute for Education and Skills (LPK) Asahi Sukoharjo. The primary data obtained through interviews. Secondary data in this study were obtained by means of literature study. Qualitative data analysis techniques based on inductive logic by observing the symptoms that exist and the reality of an event happening and principles of law that apply to the science of law. The results showed that Law No. 39 of 2004 concerning the Placement and Protection of Indonesian Workers Abroad n is not sensitive to the protection of the rights and of violence to the Indonesian Workers in South Korea. Protection of rights and abuse of Indonesian Workers (TKI) in South Korea can be done by improving the function of supervision, socialization law and custom culture, improve the functioning of legal aid, the ratification of the law of the International Convention on Migrant Workers dam seek agreement Diplomatic binding between the Government of the Republic of Indonesia with South Korea on enforcement violation of the rights and acts of violence committed services to the users of Indonesian Workers in South Korea. Keywords: Law No. 39 Year 2004 regarding the Placement and Protection of Indonesian Workers Abroad, protection of rights, violence